Approaches to considering sex and gender in continuous professional development for health and social care professionals: An emerging paradigm. (2nd September 2018) - Légaré, France; Lee-Gosselin, Hélène; Borduas, Francine; Monette, Céline; Bilodeau, André; Tanguay, Dominique; Stacey, Dawn; Gagnon, Marie-Pierre; Roch, Geneviève; Dogba, Maman Joyce; Bussières, André; Tremblay, Marie-Claude; et al.
Abstract: Consideration of sex and gender in research and clinical practice is necessary to redress health inequities and reduce knowledge gaps. As all health professionals must maintain and update their skills throughout their career, developing innovative continuing professional education programs that integrate sex and gender issues holds great promise for reducing these gaps. This article proposes new approaches to partnership, team development, pedagogical theory, content development, evaluation and data management that will advance the integration of sex and gender in continuing professional development (CPD). Our perspectives build on an intersectoral and interprofessional research team that includes several perspectives, including those of CPD, health systems, knowledge translation and sex and gender.